PROMOTING CULTURAL PRODUCTION IN SERBIA - THE CASE OF NOVI SAD - Kovačević, Mirjana Ž (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2020)
The paper presents the empirical study which aims to describe problems encountered by actors in the cultural and creative industries during the realization of ideas and activities in a modern digital environment. The results pointed out a discrep-ancy in the use of modern technology when it comes to the creation, availability and use of products of culture and creativity, and the ways they are communicated and promot-ed. Highlighting the problems that this sector faces, besides the knowledge of economic gain and overflows to other areas of the economy and society, should stimulate the interest of the competent institutions and decision-makers in finding more productive support programs for Serbian cultural and creative production in the future.